Biodynamic analysis of the uki goshi technique in judo - Nikolina Dimitrova (Exercise and Quality of Life, 2009)
Active experiment for analysis of movement activities dinamographic structure of “Uki Goshi”, one of the main ku-dan system judo techniques has been performed. The hypothesis that there are much more complicated interrelations between kinematical and dynamical structures has been proved. With the means of reacting dummy, the uke counter attack in the specific points of dynamic function development has been modeled. The untenability of classic biodynamic analysis conclusions, where the uke reaction is not modeled was proved. This study has also relation to the creation of individual training process for highly qualified competitors.